Preference and reproductivity of maize weevil, as resistance factors in some corn populations and inbreds - Santos, Jamilton P.; Foster, John E. (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this research was to determine if the populations studied could transmite their factor for resistance and susceptibility to their descendents. The experimental corn consisted of 20 different genotypes, including resistant and susceptible populations and inbreds. The infestation was made artificially. The experimental design was a randomized complete block with four replications, and three tests were established. Firstly, the distribution of the maize weevil over sample of one corn genotype, in plastic boxes, was studied. Secondly, the weevils were given a free-choice of 20 different genotypes, and the number of weevil attracted and the number of offsprings of the first generation emerged from each corn sample were observed. At last, the weevils were confined in the plastic boxes with the corn samples, and the number of offsprings emerged from each sample was observed. The results can be summarized as follows: a) the maize weevils distributed themselves evenly over the samples of same corn genotype; b) when the maize weevil had a free-choice of a corn genotype, they showed great preference for certain genotypes; c) some populations and respective inbred were resistant; d) other populations were resistant, but their respective inbred were susceptible; e) also, some populations were more susceptible than their respective inbreds.